2017
DOI: 10.1152/ajpheart.00070.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vagus nerve stimulation augments spontaneous discharge in second- and higher-order sensory neurons in the rat nucleus of the solitary tract

Abstract: Vagus nerve stimulation (VNS) currently treats patients with drug-resistant epilepsy, depression, and heart failure. The mild intensities used in chronic VNS suggest that primary visceral afferents and central nervous system activation are involved. Here, we measured the activity of neurons in the nucleus of the solitary tract (NTS) in anesthetized rats using clinically styled VNS. Our chief findings indicate that VNS at threshold bradycardic intensity activated NTS neuron discharge in one-third of NTS neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…HMNs receive strong glutamatergic inputs from several regions, including respiratory central drive from Dbx1 positive interneurons in the reticular formation (Koizumi et al, 2008 ; Revill et al, 2015 ). It is likely that these last order premotor interneurons also integrate inputs from vagal afferent-driven NTS neurons (Bailey et al, 2002 ; Bailey and Fregosi, 2006 ; Beaumont et al, 2017 ), as well as TRPV1 positive trigeminal somatosensory neurons (Cavanaugh et al, 2011 ), as in vivo studies show that respiratory rhythm drives and modulates both whisking and sniffing behaviors (Moore et al, 2013 , 2014 ). Recently, capsaicin, acting via TRPV1 receptors, has been shown to cause potent inhibition of the respiratory central pattern generator in the rhythmically active brainstem-spinal cord in vitro preparation and in plethysmographic in vivo recordings, but had no effect in a rhythmically active brainstem slice (Ren et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HMNs receive strong glutamatergic inputs from several regions, including respiratory central drive from Dbx1 positive interneurons in the reticular formation (Koizumi et al, 2008 ; Revill et al, 2015 ). It is likely that these last order premotor interneurons also integrate inputs from vagal afferent-driven NTS neurons (Bailey et al, 2002 ; Bailey and Fregosi, 2006 ; Beaumont et al, 2017 ), as well as TRPV1 positive trigeminal somatosensory neurons (Cavanaugh et al, 2011 ), as in vivo studies show that respiratory rhythm drives and modulates both whisking and sniffing behaviors (Moore et al, 2013 , 2014 ). Recently, capsaicin, acting via TRPV1 receptors, has been shown to cause potent inhibition of the respiratory central pattern generator in the rhythmically active brainstem-spinal cord in vitro preparation and in plethysmographic in vivo recordings, but had no effect in a rhythmically active brainstem slice (Ren et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of HMN activity with other upper airway muscles during oral behaviors suggests that visceral and nociceptive afferent feedback are likely to modulate HMNs or their inputs (Fregosi and Ludlow, 2014 ). Pulmonary and airway vagal afferents terminate extensively on, and activate, neurons in the nucleus tractus solitarius (NTS) and area postrema (Beaumont et al, 2017 ); these central neurons then project directly or indirectly to HMNs (Travers and Norgren, 1983 ; Bailey and Fregosi, 2006 ) (Figure 1A ). One distinguishing property of many vagal afferents is expression of the transient receptor potential vanilloid type 1 (TRPV1) receptor (Doyle et al, 2002 ; Hermes et al, 2016 ), a calcium permeable non-selective cation channel that is activated by the vanilloid capsaicin (Caterina et al, 1997 ; Messeguer et al, 2006 ), acidic pH (<6) (Tominaga et al, 1998 ), heat (Caterina et al, 1997 ) or membrane depolarization (Voets et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMNs receive strong glutamatergic inputs from several regions, including respiratory central drive from Dbx1 positive interneurons in the reticular formation (Koizumi et al, 2008;Revill et al, 2015). It is likely that these last order premotor interneurons also integrate inputs from vagal afferent-driven NTS neurons (Bailey et al, 2002;Bailey & Fregosi, 2006;Beaumont et al, 2017), as well as TRPV1…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NTS and area posterma receive pulmonary and airway vagal afferents (Beaumont et al, 2017), which show expression of the TRPV1 receptors (Doyle et al, 2002;Hermes et al, 2016). Although, TRPV1 expression is reported in several brain structures, including cortex, dentate gyrus, hypothalamus, thalamus, trigeminal somatosensory neurons and spinal cord (Mezey et al, 2000;Roberts et al, 2004;Cavanaugh et al, 2011), no TRPV1 expression has been reported in the hypoglossal motor nucleus.…”
Section: Discussionmentioning
confidence: 99%